Pengaruh Pemeliharaan Aset Dan Kualitas Pegawai Terhadap Optimalisasi Pemanfaatan Aset Di Rumah Sakit Umum Kota Tangerang Selatan - Hasim A. Abdullah; Mary Ismowati; Suprapti Widiasih; Fuji Astuti (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The background of this research is the fact that the optimization of Asset Utilization in General Hospitals in South Tangerang City has not been successful.The purpose of this study is to analyze the effect of asset maintenance and employee quality on optimization of asset utilization at a general hospital in South Tangerang City. The approach used is quantitative. This study uses the correlation method. The population in this study were employees of the General Hospital Administration of South Tangerang City. The sampling technique used is saturated sampling, the number of samples are 35 respondents. This data was analyzed using multiple linear regression analysis. The results showed that asset maintenance and employee quality had a positive and significant impact on the optimization of asset utilization at the General Hospital in South Tangerang City, either partially or simultaneously